Construction of a Polypyrrole-Based Multifunctional Nanocomposite for Dual-Modal Imaging and Enhanced Synergistic Phototherapy against Cancer Cells - Xu, Luen (Langmuir : the ACS journal of surfaces and colloids, 2019)
Design and construction of multifunctional theranostic nanoplatforms are still desired for cancer-effective treatment. Herein, a kind of polypyrrole (PPy)-based multifunctional nanocomposite was designed and successfully constructed for dual-model imaging and enhanced synergistic phototherapy against cancer cells. Through graphene oxide (GO) sheet coating, PPy nanoparticles (NPs) were effectively combined with polyethylene glycol chains, Au NPs, and IR820 molecules. The obtained PGPAI NPs showed promising ability for photoacoustic/computed tomography imaging. Under near-infrared light irradiation, the PPy core and IR820 molecule effectively generated heat and reactive oxygen species (ROS), respectively. Furthermore, the loaded Au NPs owning catalase-like activity produced oxygen by decomposing H2O2 (up-regulated in tumor region), enhancing the oxygen-dependent photodynamic therapy efficacy. The formed PGPAI NPs were also proved to own desirable photothermal conversion efficiency, photothermal stability, colloidal stability, cytocompatibility, and cellular internalization behaviors. Furthermore, cell assay demonstrated that PGPAI NPs displayed enhanced synergistic phototherapy efficacy against cancer cells. These developed multifunctional nanoplatforms are promising for effective cancer theranostic applications